2021
DOI: 10.1002/adfm.202103743
|View full text |Cite
|
Sign up to set email alerts
|

A General Ammonium Salt Assisted Synthesis Strategy for Cr3+‐Doped Hexafluorides with Highly Efficient Near Infrared Emissions

Abstract: The discovery of highly efficient broadband near infrared (NIR) emission material is urgent and crucial for constructing NIR lighting sources and emerging applications. Herein, a series of NIR emission hexafluorides A2BMF6:Cr3+ (A = Na, K, Rb, Cs; B = Li, Na, K, Cs; M = Al, Ga, Sc, In) peaking at ≈733–801 nm with a full width at half maximum (FWHM) of ≈98–115 nm are synthesized by a general ammonium salt assisted synthesis strategy. Benefiting from the pre‐ammoniation of the trivalent metal sources, the Cr3+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 53 publications
2
116
0
Order By: Relevance
“…[ 23b ] More specifically, the magnitude of tetrahedral shrinkage due to the replacement of larger Al 3+ by smaller Si 4+ is larger than that of dodecahedral expansion due to the simultaneous substitution of Ca 2+ for Y 3+ (Table S3 , Supporting Information), leading to overall shrinkage of the garnet structure (Table S1 , Supporting Information); meanwhile, the large shortening of the Si/Al—O bonds pushes the oxygen atoms of the common apex of AlO 6 octahedra away from the central Al 3+ and thus leads to the octahedral enlargement. Only when Cr 3+ occupies a large octahedral site with weak crystal field can it generate broadband NIR emission; [ 23a ] accordingly, nearly all of the reported phosphors are gallate/germanate compounds or those containing rare metal ions like Sc 3+ and In 3+ , [ 8 , 9 , 11 , 12 , 14 ] which make them high in cost. By contrast, the case of YCAS:Cr 3+ implies that it is possible to obtain weak‐field octahedral Al 3+ sites for generating broadband NIR emission with low cost.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 23b ] More specifically, the magnitude of tetrahedral shrinkage due to the replacement of larger Al 3+ by smaller Si 4+ is larger than that of dodecahedral expansion due to the simultaneous substitution of Ca 2+ for Y 3+ (Table S3 , Supporting Information), leading to overall shrinkage of the garnet structure (Table S1 , Supporting Information); meanwhile, the large shortening of the Si/Al—O bonds pushes the oxygen atoms of the common apex of AlO 6 octahedra away from the central Al 3+ and thus leads to the octahedral enlargement. Only when Cr 3+ occupies a large octahedral site with weak crystal field can it generate broadband NIR emission; [ 23a ] accordingly, nearly all of the reported phosphors are gallate/germanate compounds or those containing rare metal ions like Sc 3+ and In 3+ , [ 8 , 9 , 11 , 12 , 14 ] which make them high in cost. By contrast, the case of YCAS:Cr 3+ implies that it is possible to obtain weak‐field octahedral Al 3+ sites for generating broadband NIR emission with low cost.…”
Section: Resultsmentioning
confidence: 99%
“…Trivalent chromium ion (Cr 3+ ) [ 9 ] has shown its superiority to other activator ions [ 10 ] in emitting far‐red/NIR light of 650–1100 nm upon blue light excitation. For example, high IQE (>90%) was achieved through cation substitution [ 9c,d ] and optimizing synthesis strategy; [ 11 ] single‐phase extra‐broadband emission with FWHM > 200 nm was also realized by exploring host crystals allowing multiple‐site occupation of Cr 3+ . [ 12 ] Nevertheless, the fundamental problem for Cr 3+ activated phosphors is the small absorption cross‐section (10 −19 –10 −20 cm 2 ) of Cr 3+ as a result of the parity‐forbidden nature of intraconfigurational d–d transitions ( 4 A 2 → 4 T 1 / 4 T 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al. found Na 3 ScF 6 :Cr 3+ exhibiting an ultrahigh EQE of 40.82% and the photoelectric conversion efficiency reaching 20.94% 35 . For the Cr 3+ ‐doped broadband NIR phosphors with longer wavelength emission, however, they are usually having an inferior IQE with lower thermal quenching temperature, because the decrease of the energy gap from the excited state to the ground state may yield an increasing possibility of the non‐radiative transition 36–41 .…”
Section: Introductionmentioning
confidence: 99%
“…34 Zhang et al found Na 3 ScF 6 :Cr 3+ exhibiting an ultrahigh EQE of 40.82% and the photoelectric conversion efficiency reaching 20.94%. 35 For the Cr 3+ -doped broadband NIR phosphors with longer wavelength emission, however, they are usually having an inferior IQE with lower thermal quenching temperature, because the decrease of the energy gap from the excited state to the ground state may yield an increasing possibility of the non-radiative transition. [36][37][38][39][40][41] A novel NIR phosphor LiScP 2 O 7 :Cr 3+ has been reported by Shao et al, showing a pure broadband NIR emission peaking at 880 nm with a full width at half-maximum (FWHM) of ∼170 nm, and further improved by codoped with Yb 3+ .…”
Section: Introductionmentioning
confidence: 99%